57 THE EFFECTS OF INCREASED EXPRESSION OF FATTY ACID OXIDATION ENZYMES ON LEFT VENTRICULAR MASS AND FUNCTION IN HEART FAILURE. (1st March 2005) - Morgan, E. E.; McElfresh, T. A.; Chandler, M. P.; Young, M. E.; Stanley, W. C.; Hoit, B. D.
Abstract : Expression of cardiac fatty acid oxidation (FAO) enzymes is regulated by the nuclear transcription factor peroxisome proliferator activated receptor α (PPARα). Previous studies suggest that activation of PPARα might impair left ventricular (LV) function and increased heart failure (HF) progression. We tested the hypothesis that increased FAO enzyme expression is associated with accelerated LV dysfunction and dilation in HF. Rats underwent either left coronary artery ligation to induce HF (n = 18) or sham operation (n = 9). Eight weeks after ligation, infarcted rats were assigned treatment with fenofibrate, a PPARα agonist (150 mg/kg/day; HF + FENO, n = 9) or left untreated (HF, n = 9). After 12 weeks of treatment, rats were studied with 2-D echocardiography. LV tissue was subsequently isolated and weighed, then freeze clamped for the measurement of medium chain acyl-CoA dehydrogenase (MCAD), carnitine palmitoyl transferase I (CPT-I) and pyruvate deyhydrogenase kinase 4 (PDK-4) expression by real-time RT-PCR. Results: HF resulted in a decrease in fractional shortening (FS) and an increase in end diastolic diameter (EDD) compared to sham, and there were no differences in LV function or dilation between HF and HF + FENO groups. The LV mass (both absolute and normalized for body weight) and MCAD, CPT-I and PDK-4 expression were significantly increased in HF + FENO compared to HF and sham. There were no statistically significant differences in LV mass or mRNA expression between the HF and sham groups. Conclusion: Activation of PPARα with fenofibrate increased expression of genes of FAO enzymes and triggered a hypertrophic response without adversely affecting cardiac function or LV dilation. (Table )